Heat induced gelation of pulse protein networks. (15th July 2021) - Guldiken, Burcu; Stobbs, Jarvis; Nickerson, Michael
Highlights: CaCl2 formed stronger gels compared to NaCl and distilled water. YPC with lower hydrophobicity and high Lg/Vn ratio formed less structured gels. The least gelling concentration decreased in the presence of salts. Volume fractions were found higher at gels formed by CaCl2 solution. Abstract: This study examines the effect of salts (0.5 M NaCl or 0.25 M CaCl2 ) and protein concentration (7.5–15%) on the gel-forming abilities of lentil (LPC), yellow pea (YPC), and faba bean (FPC) protein concentrates formed at pH 7.0. The surface hydrophobicity of YPC (84.8 arbitrary units, a.u.) was found to be lower than LPC (147.2 a.u.) and FPC (135.0 a.u.). In contrast, the surface charge for LPC, YPC, and FPC was −37.8, −28.4, and −29.3 mV, respectively. The Lg/Vn ratio of YPCs was determined as 0.65 followed by LPC (0.57) and FPC (0.41). The presence of salts reduced the least gelling concentration. LPC and FPC also appeared to have a more ordered structure than YPC as evident by CLSM. The network appeared more ordered as the protein concentration increased or in the presence of NaCl or CaCl2 according to CLSM and synchrotron based micro computed tomography (µCT).